AN ECONOMIC EVALUATION OF THE PERFORMANCE EFFICIENCY OF CONSERVATION AGRICULTURE AND FOOD SECURITY PROJECTS USING LOGISTIC REGRESSION IN IRAQ FOR THE 2022-2023 SEASON - N. S. Noori; B. H. Hameed; M. Kh. Mohammed (مجلة الأنبار للعلوم الزراعية)
This research involved an economic evaluation of the performance efficiency of conservation agriculture and food security projects using logistic regression in Iraq for the 2022-2023 agricultural season. Using quantitative methodology and the logistics regression method (logit), it analyzed the main factors influencing the adoption of conservation agriculture and food security projects. Data was collected through questionnaires with 74 responses each received from farmers in the food security enhancement project and in traditional agriculture. Also, 45 forms each were received for the conservation and traditional agriculture projects. Regression model coefficients were estimated using the maximum likelihood method, explaining the dependent variable and independent variables. The dependent variable is a binary variable with a value of 1 for farmers adopting the technology and 0 for those who did not. The independent variables included age, experience, educational level, source of household income, productivity, water source, land tenure, field records, and use of agricultural technologies. The study produced several results, the most important of which is the significance of most of the variables for the two projects. The goodness-of-fit coefficient of the model was also shown using the Hosmer and Lemeshow statistic with degrees of freedom 8 d.f. The P value for the conservation agriculture and enhancing food security projects was greater than 0.05% indicating acceptance of the null hypothesis (H0) which states no difference between the observed and estimated values of the dependent variable and that the model estimates fit the data very well. The study recommended increasing government support for the dissemination of modern technologies to facilitate farmers’ access to them and intensifying training programs on the use of these technologies appropriate to the conditions of the region. This also applies to the conservation agriculture and food security projects. There is also a need to transfer the experience of the applied regions to other areas in Iraq.